Behavioral features of Wistar rats in models of autism spectrum disorders induced by prenatal or postnatal administration of sodium valproate - E. V. Savinkova; I. G. Kapitsa; T. A. Voronina (Фармакокинетика и Фармакодинамика, 2024)
Relevance. The complexity of diagnosing and treating autism spectrum disorders (ASD) is attributed to their unknown etiology and pathophysiology. The investigation of ASD models induced by sodium valproate (VPA) holds significant importance in the development of effective pharmacological interventions for this disorder.Objective. The aim of the study was to assess the impact of prenatal and postnatal exposure to VPA on the development of autism-like behavior in Wistar rats for further selection of appropriate therapeutic interventions.Methods. Offspring of Wistar rats were exposed to VPA on the 12.5th day of prenatal development or postnatally on the 14th day. Evaluation included assessment of social behavior, anxiety, working memory, species-typical defensive behavior, exploratory, and locomotor activity.Results. Prenatal VPA exposure led to reduced social interaction, increased anxiety, disruption of species-typical defensive behavior, and decreased locomotor activity in male rats. Female rats prenatally exposed to VPA exhibited social deficits, increased anxiety, hypolocomotion, and cognitive impairments, albeit without displaying aversive odor preference. Postnatal VPA exposure in male and female rats did not significantly alter social interaction and species-typical defensive behavior; however, animals exhibited reduced locomotor activity. Postnatally VPA-exposed female rats demonstrated worsened working memory and decreased exploratory behavior.Conclusion. Both prenatal and postnatal exposure to VPA elicits behavioral disturbances resembling ASD, with gender-specific nuances, which may guide the direction of pharmacological interventions for the disorder.